Impregnation versus exsolution: Using metal catalysts to improve electrocatalytic properties of LSCM-based anodes operating at 600 °C. (24th August 2016) - Thommy, Léonard; Joubert, Olivier; Hamon, Jonathan; Caldes, Maria-Teresa
Abstract: Impregnation and exsolution methods were used to improve electrocatalytic properties of LSCM towards direct oxidation of fuel at 600 °C. The electrochemical performances of three electrode materials, LSCM, nickel-doped LSCM and Ni-impregnated LSCM were compared. Electrolyte-supported symmetrical cells using Ce0.9 Gd0.1 O1.95 as electrolyte were characterized by electrochemical impedance spectroscopy. Nickel doping or impregnation leads to a reduction of polarisation phenomena, essentially related to a decreasing of gas adsorption resistance. Under hydrogen and in comparison to impregnation approach, exsolution does not offer significant advantages with regard to the polarization phenomena. The only noticeable difference concerns the electrode microstructure. Therefore, exsolution method produces a dispersion of nanoparticles firmly anchored to grain surface which minimizes nanoparticles agglomeration during ageing. Highlights: Electrocatalytic properties of LSCM towards H2 oxidation at 600 °C have been improved. Impregnation and exsolution methods were compared for adding nanocatalysts. Regarding on polarisation phenomena exsolution does not offer significant advantages. Low agglomeration exsolved nanoparticles during ageing.